2022
DOI: 10.4103/jispcd.jispcd_328_21
|View full text |Cite
|
Sign up to set email alerts
|

The Protocol of Low-level Laser Therapy in Orthodontic Practice

Abstract: A BSTRACT Low-level laser therapy (LLLT) has been widely investigated as an adjunct technique for orthodontic treatment due to photobiomodulation effect. LLLT appears to be supportive for an orthodontic practice in terms of tooth movement acceleration, pain relief, and root resorption management. The decrease in these adverse effects will enhance the compliance in orthodontic patients, which could positively impact treatment outcomes. However, there seemed to be inconsistency in the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
(236 reference statements)
0
0
0
Order By: Relevance
“…Extensive efforts have been dedicated to the development of therapies that can accelerate tooth movement, including techniques such as corticotomy and microosteoperforation. Studies conducted on animal and human models have already demonstrated that PBMT is a promising adjunctive tool for enhancing tooth movement (Figure 4), exhibiting proven efficacy and safety, and notably, no reported side effects [8,10,[37][38][39][40][41][42][43]. Orthodontic mechanics rely on the remodeling of periodontal tissue through the activation of various components, including periodontal fibroblasts, osteoblasts, osteocytes, osteoclasts, and the vascular system.…”
Section: Photobiomodulation Of Tooth Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive efforts have been dedicated to the development of therapies that can accelerate tooth movement, including techniques such as corticotomy and microosteoperforation. Studies conducted on animal and human models have already demonstrated that PBMT is a promising adjunctive tool for enhancing tooth movement (Figure 4), exhibiting proven efficacy and safety, and notably, no reported side effects [8,10,[37][38][39][40][41][42][43]. Orthodontic mechanics rely on the remodeling of periodontal tissue through the activation of various components, including periodontal fibroblasts, osteoblasts, osteocytes, osteoclasts, and the vascular system.…”
Section: Photobiomodulation Of Tooth Movementmentioning
confidence: 99%
“…Evidence suggests that laser procedures promote accelerated health recovery, enabling the patient to proceed to the next stage. Throughout the treatment, photobiomodulation therapy (PBMT) can be used for analgesia after activations, repair of traumatic ulcers, and acceleration of tooth movement [8]. Meanwhile, antimicrobial photodynamic therapy (aPDT) proves to be an effective decontamination tool for numerous clinical infections caused by viruses, fungi, and bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The diode laser wavelength of 658nm to 980nm were the most found ranges in the literature however the most common was 810nm and in clinical terms the follow-up application was at 3, 7 and 14 days for the first month and then every 15 days. The radiation points were variable from 2 to 10 points, where 10 points was the most common making an application on the buccal and lingual/palatine surface and the exposure time was variable from 10 to 300sec and the emitted energy of 25 J/cm2 [23] .…”
Section: Orthodontics 321 Painmentioning
confidence: 99%
“…The application of LLLT to accelerate tooth movement was applied immediately after the application of force. The radiation points for each point were variable according to the literature from 2 to 16 where 6 and 10 points were the most common [23] . Application of low-level laser therapy to the condylar regions accelerated functional treatment in patients with skeletal class II malocclusion by approximately 45% and increased bone growth and mandibular length [24] .…”
Section: Acceleration Of Orthodontic Movementmentioning
confidence: 99%